Spitz from the retina regulates genes transcribed in the second mitotic wave, peripodial epithelium, glia and plasmatocytes of the Drosophila eye imaginal disc. - Firth, L.C.; Baker, N.E. (Developmental Biology, 2007)
Proliferation, differentiation, and other processes must be coordinated during the development of multi-cellular animals. A discrete and regulated cell division, the Second Mitotic Wave (SMW), occurs concomitantly with early cell fate decisions in the Drosophila developing retina. Signals from the Epidermal Growth Factor Receptor (EGFR) are required to promote cell cycle arrest of specified cells and antagonize S-phase entry in the SMW. Cells that do not receive any EGFR activity enter S-phase in the SMW in response to the Notch pathway. To identify genes with potential roles in the SMW, we used microarrays and genetic manipulation of the EGFR pathway to seek transcripts regulated during the SMW. RNA in situ hybridization of 126 differentially transcribed genes revealed genes that have novel expression patterns in cells closely associated with the SMW. In addition, other genes' transcripts were regulated in the differentiating photoreceptor cells, retinal basal glia, the peripodial epithelium and blood cells (plasmatocytes) associated with the developing retina. These novel targets suggest that during eye development, EGFR activity coordinates transcriptional programs in other tissues with retinal differentiation.